U.S. cannabis legalization and use of vaping and edible products among youth. (1st August 2017) - Borodovsky, Jacob T.; Lee, Dustin C.; Crosier, Benjamin S.; Gabrielli, Joy L.; Sargent, James D.; Budney, Alan J.
Highlights: Online survey of cannabis vaping and edibles use among adolescent cannabis users. Examined relationships between vaping, edible use, and legal cannabis laws (LCL). Allowing dispensaries predicts lifetime vaping (OR: 2.7) and edible use (OR: 3.3). Allowing home growing predicts lifetime vaping (OR: 2.3) and edible use (OR: 3.0). Facebook can facilitate measurement of the impact of cannabis legalization. Abstract: Background: Alternative methods for consuming cannabis (e.g., vaping and edibles) have become more popular in the wake of U.S. cannabis legalization. Specific provisions of legal cannabis laws (LCL) (e.g., dispensary regulations) may impact the likelihood that youth will use alternative methods and the age at which they first try the method – potentially magnifying or mitigating the developmental harms of cannabis use. Methods: This study examined associations between LCL provisions and how youth consume cannabis. An online cannabis use survey was distributed using Facebook advertising, and data were collected from 2630 cannabis-using youth (ages 14–18). U.S. states were coded for LCL status and various LCL provisions. Regression analyses tested associations among lifetime use and age of onset of cannabis vaping and edibles and LCL provisions. Results: Longer LCL duration (ORvaping : 2.82, 95% CI: 2.24, 3.55; ORedibles : 3.82, 95% CI: 2.96, 4.94), and higher dispensary density (ORvaping : 2.68, 95% CI: 2.12, 3.38; ORedibles : 3.31, 95% CI: 2.56, 4.26), were related to higher likelihood of trying vaping and edibles. Permitting home cultivation was related to higher likelihood (OR: 1.93, 95% CI: 1.50, 2.48) and younger age of onset (β: −0.30, 95% CI: −0.45, −0.15) of edibles. Conclusion: Specific provisions of LCL appear to impact the likelihood, and age at which, youth use alternative methods to consume cannabis. These methods may carry differential risks for initiation and escalation of cannabis use. Understanding associations between LCL provisions and methods of administration can inform the design of effective cannabis regulatory strategies.